Determinants of Psychosocial Difficulties Experienced by Persons with Brain Disorders: Towards a 'Horizontal Epidemiology' Approach. - Carla Sabariego; Michaela Coenen; Carolina Ballert; Maria Cabello; Matilde Leonardi; Marta Anczewska; Tuuli Pitkänen; Alberto Raggi; Blanca Mellor; Venusia Covelli; Piotr Świtaj; Jonna Levola; et al. (PLoS ONE)
Background Persons with brain disorders experience significant psychosocial difficulties (PSD) in daily life, e.g. problems with managing daily routine or emotional lability, and the level of the PSD depends on social, physical and political environments, and psychologic-personal determinants. Our objective is to determine a brief set of environmental and psychologic-personal factors that are shared determinants of PSD among persons with different brain disorders. Methods Cross-sectional study, convenience sample of persons with either dementia, stroke, multiple sclerosis, epilepsy, migraine, depression, schizophrenia, substance dependence or Parkinson's disease. Random forest regression and classical linear regression were used in the analyses. Results 722 subjects were interviewed in four European countries. The brief set of determinants encompasses presence of comorbidities, health status appraisal, stressful life events, personality changes, adaptation, self-esteem, self-worth, built environment, weather, and health problems in the family. Conclusions The identified brief set of common determinants of PSD can be used to support the implementation of cross-cutting interventions, social actions and policy tools to lower PSD experienced by persons with brain disorders. This set complements a recently proposed reliable and valid direct metric of PSD for brain disorders called PARADISE24.